AUTONOMOUS ECOLOGICAL SYSTEM AS THE CONCENTRATED EMBODIMENT OF THE SIXTH ECONOMIC STRUCTURE - Olga Sandrykina (Вестник Северо-Кавказского федерального университета)
The solution of the import substitution of agricultural products and modernization of utilities by introducing of innovative technologies determines the relevance of the research work. The devices are worked out to be the tool for advanced development of agriculture and utilities.